Powering up cleaner choices: A study on the heterogenous effects of social norm-based electricity pricing on dirty fuel purchases - Salim Turdaliev (Charles University in Prague, Institute of Economic Studies (IES), 2023)
This paper examines the heterogeneous effects of the experimental introduction of increasing-block-tariffs (IBT) for residential electricity on the propensity to purchase dirty fuels using panel household data (RLMS-HSE) in a number of regions of Russia. The study demonstrates that despite the design of the IBT being based on prescribed social norms and accounting for various household and dwelling characteristics, the adverse effects of this policy (in the form of increased propensity to purchase dirty fuels) are still more pronounced among households with higher base energy consumption, those receiving subsidies for utilities, and those in a vulnerable social position where the household head's primary occupation is childcare or housekeeping. Additionally, the paper finds that households headed by females are actually 20% less likely to purchase dirty fuels due to the introduction of IBT. The findings suggest that policymakers should fine-tune the calculation of social norms to minimize the negative impacts of IBT. Furthermore, the study's results may be relevant and useful for policymakers in other developing and transition economies that aim to implement various energy reforms, including IBT.
Keywords: Q41; Q48; L98; L94; 330; residential electricity pricing; increasing-block-tariffs; heterogeneous treatment effects; social norms; dirty fuels; post-Soviet economy; Russia; natural experiment